The Need for Change: A Roadmap for the Sustainable Transformation of the Chemical Industry - Klaus Günter Steinhäuser; Markus Große Ophoff (Sustainable Chemistry)
The chemical industry faces major challenges worldwide. Since 1950, production has increased 50-fold and is projected to continue growing, particularly in Asia. It is one of the most energy- and resource-intensive industries, contributing significantly to greenhouse gas emissions and the depletion of finite resources. This development exceeds planetary boundaries and calls for a sustainable transformation of the industry. The key transformation areas are as follows: (1) Non-Fossil Energy Supply: The industry must transition away from fossil fuels. Renewable electricity can replace natural gas, while green hydrogen can be used for high-temperature processes. (2) Circularity: Chemical production remains largely linear, with most products ending up as waste. Sustainable product design and improved recycling processes are crucial. (3) Non-Fossil Feedstock: To achieve greenhouse gas neutrality, oil, gas, and coal must be replaced by recycling plastics, renewable biomaterials, or CO2-based processes. (4) Sustainable Chemical Production: Energy and resource savings can be achieved through advancements like catalysis, biotechnology, microreactors, and new separation techniques. (5) Sustainable Chemical Products: Chemicals should be designed to be “Safe and Sustainable by Design” (SSbD), meaning they should not have hazardous properties unless essential to their function. (6) Sufficiency: Beyond efficiency and circularity, reducing overall material flows is essential to stay within planetary boundaries. This shift requires political, economic, and societal efforts. Achieving greenhouse gas neutrality in Europe by 2050 demands swift and decisive action from industry, governments, and society. The speed of transformation is currently too slow to reach this goal. Science can drive innovation, but international agreements are necessary to establish a binding framework for action.